고립파(지진해일)의 파형분포가 불투과 경사면의 처오름에 미치는 영향 - 이우동(Woo-Dong Lee); 김정욱(Jung-Ouk Kim); 허동수(Dong-Soo Hur) (Han-guk haeyang gonghak hoeji (Online), 2019)
For decades, solitary waves have commonly been used to simulate tsunami conditions in numerical studies. However, the main component of a tsunami waveform acts at completely different spatial and temporal distributions than a solitary waveform. Thus, this study applied a 2-D numerical wave tank that included a non-reflected tsunami generation system based on Navier-Stokes equations (LES-WASS-2D) to directly simulate the run-up of a tsunami-like solitary wave on a slope. First, the waveform and velocity due to the virtual depth factor were applied to the numerical wave tank to generate a tsunami, which made it possible to generate the wide waveform of a tsunami, which was not reproduced with the existing solitary wave approximation theory. Then, to validate the applied numerical model, the validity and effectiveness of the numerical wave tank were verified by comparing the results with the results of a laboratory experiment on a tsunami run-up on a smooth impermeable 1:19.85 slope. Using the numerical results, the run-up characteristics due to a tsunami-like solitary wave on an impermeable slope were also discussed in relation to the volume ratio. The maximum run-up heights increased with the ratio of the tsunami waveform. Therefore, the tsunami run-up is highly likely to be underestimated compared to a real tsunami if the solitary wave of the approximation theory is applied in a tsunami simulation in a coastal region.